Unconjugated secondary bile acids activate the unfolded protein response and induce golgi fragmentation via a src-kinase-dependant mechanism - GILMER, JOHN; LONG, AIDEEN; Sharma, Ruchika; Quilty, Francis; Byrne, Anne-Marie (My University, 2017)
Bile acids are components of gastro-duodenal refluxate and regarded as causative agents in oesophageal disease but the precise mechanisms are unknown. Here we demonstrate that a specific subset of physiological bile acids affect the protein secretory pathway by inducing ER stress, activating the Unfolded Protein Response (UPR) and causing disassembly of the Golgi apparatus in oesophageal cells. Deoxycholic acid (DCA), Chemodeoxycholic acid (CDCA) and Lithocholic acid (LCA) activated the PERK arm of the UPR, via phosphorylation of eIF2α and up-regulation of ATF3, CHOP and BiP/GRP78. UPR activation by these bile acids is mechanistically linked with Golgi fragmentation, as modulating the UPR using a PERK inhibitor (GSK2606414) or salubrinal attenuated bile acid-induced effects on Golgi structure. Furthermore we demonstrate that DCA, CDCA and LA activate Src kinase and that inhibition of this kinase attenuated both bile acid-induced BiP/GRP78 expression and Golgi fragmentation. This study highlights a novel mechanism whereby environmental factors (bile acids) impact important cellular processes regulating cell homeostasis, including the UPR and Golgi structure, which may contribute to cancer progression in the oesophagus.
PUBLISHED
Keywords: Bile acid; Unfolded protein response; ER stress; Golgi apparatus; Oesophageal cancer; Cancer